2013
DOI: 10.1111/jocn.12256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noninvasive electroacupuncture on labour pain and duration

Abstract: Noninvasive electroacupuncture on the LI4 acupuncture point could be used easily during labour for labour pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 19 publications
0
35
1
1
Order By: Relevance
“…Acupuncture has been documented to have many actions throughout the body including 1) deactivation of the limbic-paralimbic-neocorticol network system, which among other things is responsible for the perception of sensory pain 11,12 ; 2) activation of mu opioid receptors 13,14 ; 3) increase in serum ␤ endorphins 15-17 ; 4) increase in adrenocorticotropic hormone (ACTH) release from the anterior pituitary, thus decreasing pain 15,18 ; 5) downregulation of M1 macrophages, Interleukin-1␤, Interleukin-6, Interleukin-18, and tumor necrosis factor (TNF), which have inflammatory functions 15,17,19-21 ; 6) upregulation of M2 macrophages, which have anti-inflammatory functions and increase immune system function of phagocytes, lymphocytes, T cells, B cells, and NK cells 15,17,19 ; and 7) during labor, stimulation of release of oxytocin from the posterior pituitary. 15,22 It is presumed by researchers and those practicing acupressure that the mechanisms of acupressure and acupuncture are similar.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Acupuncture has been documented to have many actions throughout the body including 1) deactivation of the limbic-paralimbic-neocorticol network system, which among other things is responsible for the perception of sensory pain 11,12 ; 2) activation of mu opioid receptors 13,14 ; 3) increase in serum ␤ endorphins 15-17 ; 4) increase in adrenocorticotropic hormone (ACTH) release from the anterior pituitary, thus decreasing pain 15,18 ; 5) downregulation of M1 macrophages, Interleukin-1␤, Interleukin-6, Interleukin-18, and tumor necrosis factor (TNF), which have inflammatory functions 15,17,19-21 ; 6) upregulation of M2 macrophages, which have anti-inflammatory functions and increase immune system function of phagocytes, lymphocytes, T cells, B cells, and NK cells 15,17,19 ; and 7) during labor, stimulation of release of oxytocin from the posterior pituitary. 15,22 It is presumed by researchers and those practicing acupressure that the mechanisms of acupressure and acupuncture are similar.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Hantoushzadeh et al [21] and Ziaei and Hajipour [22] obtained similar results in 2007 and 2006, respectively, showing decreased visual analog pain scale score in women receiving acupuncture during labor. In the most recent study, the authors detected no statistically significant decrease in pain or duration of labor, although mean pain score and labor duration were lower in the acupuncture group [23]. Serum cortisol level rises significantly during the stressful condition of labor.…”
Section: Discussionmentioning
confidence: 95%
“…We found one study that investigated the role of electroacupuncture on cortisol level in labor. The authors reported that there was lower adrenocortical hormone and cortisol levels in the electroacupuncture group, although the difference did not reach a statistically significant level [26].…”
Section: Discussionmentioning
confidence: 96%
“…We found one meta-analysis of randomized trials published in the Cochrane database in 2011 and 6 randomized trials published since then [91][92][93][94][95][96][97]. Of the 6 trials, only 4 reported oxytocin use [94][95][96][97].…”
Section: Acupuncture and Acupressurementioning
confidence: 99%